2019
DOI: 10.1002/jsfa.9811
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical composition and biological activities of differently pigmented cabbage (Brassica oleracea var. capitata) and cauliflower (Brassica oleracea var. botrytis) varieties

Abstract: Phytochemical composition and biological activities of differently pigmented cabbage (Brassica oleracea var. capitata) and cauliflower (Brassica oleracea var. botrytis) varieties Abstract BACKGROUND: Brassica plants contain a wide spectrum of bioactive components that are responsible for their health-promoting potential such as vitamins, polyphenols and glucosinolates. This study attempted to relate the composition of bioactive phytochemicals and chosen biological activities (antioxidant, cytotoxic, anti-genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…We expected that colored varieties, because of the presence of anthocyanins (which belong to very strong plant antioxidants), would exhibit higher antioxidant capacity. This hypothesis was proved by previous studies of Sumaya-Martinez [15], Sanchez-Sulcedo et al [16], Matsafiji et al [13], Kim et al [18], Garcia-Lafuente et al [19], Koss-Mikołajczyk et al [9], and Koss-Mikołajczyk et al [20] that showed that antiradical activity was significantly correlated with the concentration of redox active compounds. This turned out not to be the case for RGra in batch spectrophotometric tests (Figure 2), although antioxidant profiles revealed substantial antioxidant activity of RGra pigments.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We expected that colored varieties, because of the presence of anthocyanins (which belong to very strong plant antioxidants), would exhibit higher antioxidant capacity. This hypothesis was proved by previous studies of Sumaya-Martinez [15], Sanchez-Sulcedo et al [16], Matsafiji et al [13], Kim et al [18], Garcia-Lafuente et al [19], Koss-Mikołajczyk et al [9], and Koss-Mikołajczyk et al [20] that showed that antiradical activity was significantly correlated with the concentration of redox active compounds. This turned out not to be the case for RGra in batch spectrophotometric tests (Figure 2), although antioxidant profiles revealed substantial antioxidant activity of RGra pigments.…”
Section: Discussionmentioning
confidence: 70%
“…However, pigments are not the only antioxidant phytochemicals, though they indeed frequently show stronger antioxidant potential than other redox active compounds (e.g., phenolic acids, flavan-3-ols, etc.) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, using HPLC-DAD-MS/MS, Wiczkowski et al [249] identified twenty cyanidin derivatives, with cyanidin-3-diglucoside-5-glucoside as the base structure, and cyanidin-3-diglucoside-5-glucoside, cyanidin-3-(sinapoyl)(sinapoyl)-diglucoside-5-glucoside, and cyanidin-3-(p-coumaroyl)-diglucoside-5-glucoside were the most abundant non-acylated anthocyanins. Moreover, Koss-Mikołajczyk et al [250] identified nineteen different cyanidin derivatives, with cyanidin-3-(feruloyl)-diglucoside-5-glucoside and cyanidin-3-(sinapoyl)(sinapoyl)-diglucoside-5-glucoside having been the most predominant. Similar results were obtained by other authors, who however using different analytical procedures and equipment identified a lower number of anthocyanins [19,251].…”
Section: Cabbage and Kalementioning
confidence: 99%
“…Comparing the biological activities (antioxidant, cytotoxic, anti-genotoxic, and influence on enzymatic activities) of the extract of green and red cabbage Koss-Mikołajczyk et al [250] found that the anthocyanin content and profile was highly correlated with the antioxidant capacity of tested plant extracts measured through different spectrophotometric assays (ABTS, FC, DPPH, and FRAP), and by testing the cellular antioxidant activity. Instead, all the other biological activities tested were not correlated with the content of neither anthocyanins nor glucosinolate derivatives, suggesting that the food matrix effect may be more relevant than the biological activity of the single compound.…”
Section: Cabbage and Kalementioning
confidence: 99%